Pengaruh Literasi Keuangan, Norma Subjektif, dan Gaya Hidup terhadap Perilaku Konsumtif Mahasiswa UIN SU Medan Pengguna Electronic Money dengan Pengendalian Diri sebagai Moderasi - Nabil Al Arif; Imsar Imsar (Transformasi Manageria: Journal of Islamic Education Management, 2023)
This study aims to analyze the effect of financial literacy, subjective norms, and lifestyle on the consumptive behavior of UIN SU students using electronic money with self-control as a moderating variable. The research method used is a quantitative method with an accidental sampling technique. The data analysis technique used is the SPSS 26 Moderated Regression Analysis (MRA) test. The results show that financial literacy has no significant and negative effect on student consumptive behavior by 9.4%, subjective nor ms have a positive and significant effect on student consumptive behavior by 22, 9%, and lifestyle has a positive and significant effect on the consumptive behavior of students by 41.8%. Financial literacy, subjective norms, and lifestyle simultaneously have a positive and significant effect on student consumptive behavior with a significance value obtained reaching 0.000 < 0.05, and Fcount greater than Ftable (15.907 > 2.47). Self-control has a significant effect on consumptive behavior with a significance value obtained of 0.021 <0.05, and tcount is greater than ttable (2,341> 1,985). Self-control does not strengthen financial literacy, subjective norms, and lifestyles on consumptive behavior. In addition, self-control affects consumptive behavior, so it can be concluded that self-control can influence consumers in choosing goods for consumption. Keywords: Consumptive Behavior; Financial Literacy; Subjective Norm; Lifestyle; Self Control